Fibro-porous PLLA/gelatin composite membrane doped with cerium oxide nanoparticles as bioactive scaffolds for future angiogenesis. Issue 39 (15th September 2020) - Xu, Zhiyang; Xu, Yulong; Basuthakur, Papia; Patra, Chitta Ranjan; Ramakrishna, Seeram; Liu, Yong; Thomas, Vinoy; Nanda, Himansu Sekhar
Abstract : Functionalized cerium oxide nanoparticle (CeNP)-loaded fibro-porous poly-l -lactic acid (PLLA)/gelatin composite membranes were prepared via electrospinning Abstract : Functionalized cerium oxide nanoparticle (CeNP)-loaded fibro-porous poly-l -lactic acid (PLLA)/gelatin composite membranes were prepared via an electrospinning technology. Considering the importance of such membrane scaffolds for promoting angiogenesis in tissue engineering and drug screening, a series of PLLA/gelatin composite fiber membranes loaded with different doses of CeNPs was prepared. The prepared composite membranes demonstrated hydrophilicity, water absorption, and improved mechanical properties compared to a PLLA and PLLA/gelatin membrane. Also, cell viability assay using somatic hybrid endothelial cells (EA.hy926) proved the biocompatible nature of the scaffolds. The biocompatibility was further supported by in vivo chick embryo angiogenesis assay using fertilized eggs. Our initial results support that these membrane scaffolds could be useful for angiogenesis-related disease treatment after further investigations.